Kajian Alat Pemipil Jagung di Tingkat Petani - Sudirman Umar (agriTECH, 2003)
In general, shelling activity has been carried out mechanically by corn-sheller. Due to lowest capacity and high value of broken grain, manual shelling has been left. Post harvest processing needs mechanical technology input like corn-sheller to reduce broken grain and emphasize the lost. Efficient corn sheller and reached to be developed. The object study of two corn-sheller was conducted in May 2000 at center corn production. Tanah Laut regency South Kalimantan was studying technical and economical feasibility of corn-sheller on farmer level. The study has used experiment and mean score method with four replications. For each the machine testing using BIN-2 variety. 200 kg/testing with 17 – 23% wet basis moisture content was use in this experiment. Financial analysis has used for calculating investment cost, break event point and pay back period, net present value, benefit cost ratio and internal rale of return. The result showed that performance of PIJAG-288 corn-shelter has higher efficiency value and pure grain percentage and also lower percentage of mixed and broken grain. Base on shelling cost Rp. 15.00. would be obtained unit cost Rp. 6,57/kg, break event point 51.94 ton/year. net present value (NPV) as Rp. 1L66 million, with 17.57% of internal rate of return (IRR). Base on financial analysis especially in cost production and NPV, PIJAG-288 more benefit than AGR-920. It has pay back period .(PBP) more less than one year. Advanced analysis using economic feasibility analysis indicates technology ofcorn-sheller to applied with B/C ratio 1.86 (pijag-288) and 1.48 (agr-920)